Importancia de la gestión interna empresarial en la empresa - Portempo Ltda. (2021)
Knowledge management is the effort made by an organization to increase, acquire, organize, distribute and share knowledge among employees, this in order to give added value to each company, company or organization that is governed by this new knowledge. We can find types of knowledge such as tacit and explicit.In front of my knowledge, I consider that explicit knowledge is valued monetarily in companies and companies since it is by mathematical part that business income is generated, thus being the reason why a company can continue to operate, bearing in mind that tacit knowledge can lead to business advancement or growth and also generate monetary income.